Tracking progress and generating accountability for global food system commitments - Nordhagen, Stella; Fanzo, Jessica (International Food Policy Research Institute, 2023)
Central to understanding the political economy of food systems transformation is clarifying the systems that enable—or prevent—monitoring progress on transformation, setting evidence-based commitments for improvement, and ensuring accountability for delivering on them. Prior chapters in this volume have elucidated the role of data and evidence in settling fact-based policy disagreements (Chapter 2) and described some of the challenges that arise when disinformation and bias instead dominate policy discussions (Chapter 1). They have also given specific examples of how evidence can galvanize attention to an issue, as in the case of obesity prevention (Chapters 6 and 7) or environmental sustainability (Chapter 11), or support the case for policy change, as in the case of agricultural subsidies or direct payments (Chapters 3 and 4). And they have highlighted the need to track how well policies are implemented (Chapter 6) as well as their intended and unintended consequences (Chapter 3). Jointly, the prior chapters have made clear that monitoring food system transformation can play a central role in several different political economy spaces described in the first chapter of this volume, such as policy mobilization, design, and adaptation. This chapter thus builds on this foundation to examine prior attempts at monitoring food systems and ensuring accountability. After highlighting existing gaps and why new approaches are needed, we present selected options for filling these gaps. We then conclude with a discussion of what else, besides information, is needed to foster the broader accountability cycle—and thus to support the process of food system transformation amid the types of political economy challenges described in the prior challenges.